2021
DOI: 10.3390/info12100391
|View full text |Cite
|
Sign up to set email alerts
|

Information Content Measurement of ESG Factors via Entropy and Its Impact on Society and Security

Abstract: We conducted a singular and sectoral vulnerability assessment of ESG factors of Dow-30-listed companies by applying the entropy weight method and analyzing each ESG factor’s information contribution to the overall ESG disclosure score. By reducing information entropy information, weaknesses in the structure of a socio-technological system can be identified and improved. The relative information gain of each indicator improves proportionally to the reduction in entropy. The social pillar contains the most cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The relative performance of each sector to the average sector performance was analysed to determine which sectors communicate ESG well, and which sectors distort the information content of the corresponding ESG measure. The study found that the healthcare, defence, and automotive sectors are conveying unclear messaging within the environmental and social pillar, while the financial, consumer goods, and industrial sectors convey messages very efficiently in these pillars [43]. Another key finding was that sectors with clear, lean, and flexible governance structures, such as automotive, IT, and travel, are most effective in messaging [43].…”
Section: Esg and Different Industriesmentioning
confidence: 96%
See 2 more Smart Citations
“…The relative performance of each sector to the average sector performance was analysed to determine which sectors communicate ESG well, and which sectors distort the information content of the corresponding ESG measure. The study found that the healthcare, defence, and automotive sectors are conveying unclear messaging within the environmental and social pillar, while the financial, consumer goods, and industrial sectors convey messages very efficiently in these pillars [43]. Another key finding was that sectors with clear, lean, and flexible governance structures, such as automotive, IT, and travel, are most effective in messaging [43].…”
Section: Esg and Different Industriesmentioning
confidence: 96%
“…The study found that the healthcare, defence, and automotive sectors are conveying unclear messaging within the environmental and social pillar, while the financial, consumer goods, and industrial sectors convey messages very efficiently in these pillars [43]. Another key finding was that sectors with clear, lean, and flexible governance structures, such as automotive, IT, and travel, are most effective in messaging [43].…”
Section: Esg and Different Industriesmentioning
confidence: 96%
See 1 more Smart Citation
“…Depending on the entropy measure used, all of these have been applied in many different areas of knowledge, such as physics [20], information theory [21,22], complexity theory [23][24][25], security [26][27][28], biology [29][30][31][32], finances [33], and medicine [34][35][36], among others. The conditional Tsallis entropy, as suggested in Reference [37], can be directly applied to information theory, especially coding theory.…”
Section: Introductionmentioning
confidence: 99%